Diversity, distribution, and conservation status of Rubiaceae species in Peñablanca Protected Landscape and Seascape, Luzon, Philippines - Rachel Biag; GRECEBIO JONATHAN D. ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Biag RA, Alejandro GJD. Diversity, distribution, and conservation status of Rubiaceae species in Peñablanca Protected Landscape and Seascape, Luzon, Philippines. Biodiversitas 22: 3627-3636. Peñablanca Protected Landscape and Seascape (PPLS) is the largest protected area (PA) in the province of Cagayan, Luzon, Philippines. As part of the Sierra Madre Mountain Range and being contiguous with the Northern Sierra Madre Natural Park, there is no doubt that this PA would display species endemism and richness. Hence, botanical surveys through purposive sampling in seven barangays/districts were conducted in the PPLS to determine the species diversity and distribution of Rubiaceae. This study also aims to identify the endemic species and determine their conservation status. Forty-two species of Rubiaceae belonging to 19 genera and 13 tribes were documented in the current study. The most species-rich tribes are Spermacoceae (9 sp.), followed by Psychotrieae (7 sp.), Pavetteae (6 sp.), Naucleae (5 sp.), Ixoreae (4 sp.), Aleisantheae (2 sp.), Mussaendeae (2 sp.), and Vanguerieae (2 sp.). The rest of the tribes, i.e., Augusteae, Coffeeae, Gardenieae, Knoxieae, and Morindeae, are represented by a single species. Minanga, Nabbabalayan and Sisim harbor the most species. Results show that 19 Philippine endemic species are thriving in the PPLS. Of these, four are threatened species; one is near threatened, three being least concern, two as data deficient, and the rest were not evaluated.